Anafora Dalam Puisi “ Jendela Dunia “Antologi Puisi Syair Burung Beo - Kasma Amin; Rahmi Usman (Tamaddun Life, 2018)
Writing poetry for ordinary people is still a complicated thing. The challenge that is often felt is the use of language style in the creation of poetry. The author often does not understand the right style of language for a work of poetry. Many language styles are chosen in the creation of poetry and as a channeling of ideas. One style of language is the Anafora form. The purpose of this writing is to describe the forms of anaphora in poetry. The benefits of writing are finding forms of anaphora in poetry and can apply them in the form of writing poetry. The writing method used is descriptive qualitative research. The results of the discussion showed the existence of anaphorous forms in the poetry window of the world.